1994
DOI: 10.1001/archsurg.1994.01420290029004
|View full text |Cite
|
Sign up to set email alerts
|

Age Does Not Predict Breast Cancer Outcome

Abstract: In conclusion, younger patients as a group have more aggressive and advanced breast cancer at presentation compared with older patients. Considered in a multivariate model, together with other variables, age does not provide independent prognostic information and should not be used alone for management decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 23 publications
3
25
0
Order By: Relevance
“…This decision was intended to avoid well-known problems with the optimal cutpoints approach . Our estimated FP function seems to explain the current discussion about several cutpoints for young age which range at least from 33 (Rochefordiere et al, 1993) to 45 (Crowe et al, 1994;Collett et al, 1996). Moreover, our results give some indication that the effect of age is sometimes not established because of differences in statistical approaches.…”
Section: Discussionsupporting
confidence: 71%
“…This decision was intended to avoid well-known problems with the optimal cutpoints approach . Our estimated FP function seems to explain the current discussion about several cutpoints for young age which range at least from 33 (Rochefordiere et al, 1993) to 45 (Crowe et al, 1994;Collett et al, 1996). Moreover, our results give some indication that the effect of age is sometimes not established because of differences in statistical approaches.…”
Section: Discussionsupporting
confidence: 71%
“…These results are similar to those in previous studies in which cases were not selected to control for histologic grade or type. 3,8,12,49 Although the premenopausal women in our study presented with a higher stage of disease, overall survival in the pre-and postmenopausal women was similar. When comparing overall survival in women with high-and low-grade carcinomas, those with highgrade carcinomas had a worse prognosis, but, unexpectedly, this difference was largely a result of the particularly poor outcome of premenopausal women with high-grade carcinomas.…”
Section: Hormone Receptors and Breast Cancer Proliferationmentioning
confidence: 55%
“…Other studies (29,30) have demonstrated that after controlling for stage, prognosis is unchanged regardless of age at diagnosis. Still other studies have demonstrated that while prognosis may be more closely related to stage at diagnosis than to age at diagnosis, younger women are more likely to present with advanced stage tumors than older women (31), and that the primary tumors of younger women are more likely to be associated with poor prognostic features, such as hormone receptor negativity, mitotic activity, and oncogene overexpression (10,15). Adding further confusion to these issues is the fact that there is no uniform definition for "early onset" breast cancer, with different studies using ages ranging from 30 to 50 years as cutoff points.…”
Section: Subsetmentioning
confidence: 99%